Proceedings of Universiti Sains Malaysia International Conference on Social Sciences 2015 - Touching Lives, Bridging Society - PPSKM, Pusat Pengajian Sains Kemasyarakatan (Universiti Sains Malaysia, 2015)
A society and people in general have always been the major focus of any study in the field of social sciences. Given the conflicts, competition, pressures, tensions and differences that are prevalent and persisting around us in today‘s society, social scientists can have a great potential to touch the lives of all human beings in many different societies. By doing so, they too can bridge the gaps that are seen to be widening between and within societies today. The field of social sciences critically examines and analyses elements of human existence, their infinite combinations of interactions, their value systems, traditions, culture, options and choices and practices. This is reflected in a broad range of disciplines which include anthropology and sociology, development studies, economics, political science, psychology and social work. The proceedings of this conference includes papers presented at the USM-International Conference on Social Sciences (USM-ICOSS) 2015 which was hosted with the aptly noble theme ―Touching Lives and Bridging Society‖ and held from 27 - 28 August 2015 at the Rainbow Paradise Beach Resort, Penang, Malaysia. This conference is solely organized by the School of Social Sciences, Universiti Sains Malaysia (USM), Malaysia.